From Carers to Trainers: Professional Identity and Body Work in Rehabilitative Eldercare. Issue 1 (3rd February 2016) - Meldgaard Hansen, Agnete; Kamp, Annette
Abstract : This article explores how a nationwide reform initiative, calling for a rehabilitative, activating and 'training' approach to elderly people in Danish homecare services, may transform gendered and embodied conceptions of 'the professional care worker'. Care work for the elderly is a low‐paid and low‐status occupation, affected by the stigma connected with elderly bodies. Drawing on an ethnographic case study of a homecare unit, this article shows how the adoption of a new distanced, goal‐oriented approach to elderly bodies attempts to transform professional identities, and how care work is constructed as reflexive and change oriented, in contrast to emotional and relational approaches. This transformation potentially leads to a more advantageous position for care workers in gendered professional hierarchies. Simultaneously this process seems to render care workers' own bodies more visible, problematizing what are perceived as uncontrolled and unhealthy care worker bodies. The article thus argues that rehabilitative eldercare leads to an intertwining of two forms of bodywork, where work on the care worker's own body and the elderly body mutually constitute each other in a novel body–body articulation.